Case Report: Myocarditis After COVID-19 Vaccination – Case Series and Literature Review - Nunn, Samuel; Kersten, Johannes; Tadic, Marijana; Wolf, Alexander; Gonska, Birgid; Hüll, Elina; Dietenberger, Hanna; Rottbauer, Wolfgang; Buckert, Dominik (Frontiers in Medicine, 2022)
Background: The ongoing COVID-19 pandemic demands a series of measures and, above all, the vaccination of a substantial proportion of the population. Acute myocarditis is a rare complication of the widely used mRNA-based vaccines. Case Presentation: We present a case series of four patients (three men and one woman, 16 to 47 years old) with acute pericarditis/myocarditis 3 to 17 days after mRNA vaccination. They presented with chest pain, fever, and flu-like symptoms. Diagnosis was made based on the synopsis of clinical presentation, elevated levels of troponin T and NT-proBNP, impaired systolic function on echocardiography, and findings in noninvasive tissue characterization by cardiovascular magnetic resonance imaging. Two patients also underwent endomyocardial biopsies. As none of the patients showed signs of cardiogenic shock, they were discharged from ward care only a few days after their initial presentations. Conclusions: Our data are consistent with other case reports of myocarditis early after mRNA vaccination and demonstrate the need for multimodal diagnostics. In view of its rarity and mild course, the risk–benefit ratio of vaccination remains positive compared to potential SARS-CoV-2 infection.